DETEKSI PENGHINDARAN PAJAK: LEVERAGE, RETURN ON ASSET, UKURAN PERUSAHAAN, DAN KEPEMILIKAN INSTITUSIONAL DI INDONESIA - Kartika, Andi; Fitriati, Ika Rosyada (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
This study examines the effect of leverage, Return On Assets (ROA), firm size, and institutional on tax avoidance. This study uses the subject of manufacturing companies listed on the Indonesia Stock Exchange with a research period of 2020 to 2022. The total sample used in this study is 75 manufacturing companies with a research period of 3 years. The sample was selected by purposive sampling method. The relationship and influence between variables is explained using multiple regression analysis method. The results showed that return on assets and firm size had a positive effect on tax avoidance, meanwhile, leverage and institutional have not been able to prove their influence on tax avoidance.